Resuming Elective Orthopaedic Surgery During the COVID-19 Pandemic: Guidelines Developed by the International Consensus Group (ICM). (15th July 2020) - Parvizi, J.; Gehrke, T.; Krueger, C.A.; Chisari, E.; Citak, M.; Van Onsem, S.; Walter, W.L.; Abdelaziz, H.; Abolghasemian, M.N.; Aboltins, C.; Al Maskari, S.M.; Baldini, A.; et al.
Abstract : As we resume elective surgical procedures, it is important to understand what practices and protocols should be altered or implemented in order to minimize the risk of pathogen transfer during the severe acute respiratory syndrome (SARS)-CoV-2 pandemic. Each hospital and health system should consider their unique situation in terms of SARS-CoV-2 prevalence, staffing capabilities, personal protection equipment supply, and so on when determining how and when to implement these recommendations. All patients should be screened for SARS-CoV-2 by means of a thorough history and physical examination, as well as reverse transcription-polymerase chain reaction (RT-PCR) testing whenever possible, prior to undergoing elective surgery. Patients who are currently infected with coronavirus disease 2019 (COVID-19) should not undergo elective surgery. These guidelines are based on the available scientific evidence, albeit scant. The recommendations have been reviewed and voted on by the expert delegates who produced this document.